Formative Assesment in the Classroom: Discursive Analysis of the Feedback Activity in Supervised Practice of Undergraduate Educational Psychologists - Jorge Alberto Moreno Ruiz; Antonia Candela Martín; Patricia Bañuelos Lagunes (Universidad Autónoma de Madrid, 2019)
This is a discursive study of the formative assessments as feedback activities that take place as part of the Supervised Practice of undergraduate educational psychologists at a Mexican public university (UNAM). The formative practice of undergraduate psychologists has been recognized as very important, however there are few studies that show how are they evaluated as a formative practice at the classroom. Analyze the processes of interactional work involved in a feedback activity, when students become evaluators of competence or psycho-educational skills, in modalities of formative assessment such as (a) co-evaluation, (b) peer evaluation and (c) self-evaluation, is this work purpose. After the first psycho-educative session at the Gesell camera several classroom interactional extracts were analysed, where the participants (the teacher, an intern and undergraduates) evaluate the professional competence of an undergraduate student that work as the psychologist of a particular case. A discursive approach informed by the ethnometodology and the conversation analysis perspective orients the study in order to exam, turn by turn, the formative assessments of the undergraduate psychologists work and the public positions about her performance. The analysis results show the collective construction of the formative assessments of the supervised practice realised by a psychologist student. This psychologist together with a passant are in charge of the case and the rest of the students observe and participate in the assessment of the supervised practice. Through these collective discursive processes, all the participants have the opportunity to improve their professional performance. This results show the important contribution of this kind of analysis in order to describe and recognize the formative contribution of the supervised practices evaluated in real settings.